Love and the Patriarch: Augustine and (Pregnant) Women. (19th August 2016) - Grosse, Patricia L.
Abstract : Theories concerning love in the West tend to be bound by the problematic constraints of patriarchal conceptions of what counts ontologically as "true" or "universal" love. It seems that feminist love studies must choose between shining light on these constraints or bursting through them. In this article I give a feminist analysis of Augustine of Hippo's theory of love through a philosophical, psychological, and theological reading of his complicated relationships with women. I argue that, given the "embodied" nature of his many loves throughout his life, there is room in Augustine's account of love for a gendered reading of love that is unconstrained by patriarchal notions concerning which gender is capable of which kind of love. Augustine's theory of love is one that is not coldly universal but bodied and personal; indeed, although it is founded inside patriarchal historical constructions, it is capable of bursting out of these constraints and suggesting an egalitarian, nongendered view of love.